2021
DOI: 10.21037/jgo-20-374
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of laparoscopic versus open total gastrectomy after neoadjuvant chemotherapy: a cohort study using the propensity score matching method

Abstract: Background: Until now, little is known about the benefit of laparoscopic total gastrectomy (LTG) after neoadjuvant chemotherapy (NACT). This study was designed to compare the safety and efficacy of the LTG versus the open total gastrectomy (OTG) approach after NACT treatment in patients with advanced gastric cancer (AGC).Methods: This study involved a cohort of 145 patients with AGC who underwent total gastrectomy after NACT at our centre between April 2013 and August 2018 including 24 cases of LTG and 121 OTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 58 publications
0
19
1
Order By: Relevance
“…11 studies [ 18 28 ] reported the incidence of postoperative complications, 12 studies [ 18 – 22 , 24 30 ] reported the duration of surgery, 4 studies [ 20 – 22 , 25 ] reported the incidence of postoperative liver failure, 10 studies [ 18 21 , 24 , 25 , 27 30 ] reported the amount of intraoperative bleeding, 5 studies [ 18 , 21 , 22 , 24 , 27 ] reported survival rates, and 4 studies [ 18 , 21 , 24 , 29 ] reported recurrence rates. A total of 1616 patients were included, including 795 patients in the 2D group and 819 patients in the 3D group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11 studies [ 18 28 ] reported the incidence of postoperative complications, 12 studies [ 18 – 22 , 24 30 ] reported the duration of surgery, 4 studies [ 20 – 22 , 25 ] reported the incidence of postoperative liver failure, 10 studies [ 18 21 , 24 , 25 , 27 30 ] reported the amount of intraoperative bleeding, 5 studies [ 18 , 21 , 22 , 24 , 27 ] reported survival rates, and 4 studies [ 18 , 21 , 24 , 29 ] reported recurrence rates. A total of 1616 patients were included, including 795 patients in the 2D group and 819 patients in the 3D group.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies reported intraoperative blood loss [ 18 21 , 24 , 25 , 27 30 ]. The meta-analysis of random effects model showed that intraoperative blood loss in the 3D group was less than that in the 2D group (SMD = −63.85, 95% CI = −98.66–29.04, P =0.0003), and the difference between the two groups was statistically significant ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…STOMACH trial showed no significant difference in the rate of postoperative complications between OTG (42.9%) and LTG (34.0%) in LTG after NACT in Western countries ( P = 0.408). Wang et al [ 30 ] demonstrated that LTG had comparable safety to OTG after NACT in the perioperative period and patients in the LTG group could benefit from less intravenous patient-controlled analgesia (IV-PCA) use[ 30 ]. Back to our study, we found that LTG did not significantly increase or decrease 30-d postoperative complications compared with OTG after NACT (overall morbidity of LTG vs OTG: 23.0% vs 28.0%, P = 0.503; severe morbidity of LTG vs OTG: 3.3% vs 2.7%, P = 1.000), which was similar to the results of the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%